Influence of imidazolinones alone and in combination on pigeonpea (Cajanus cajan) - Kumar, Amit; Dhaka, A K; Kumar, Satish; Singh, Samunder; Ishmadhu, Ishmadhu; Singh, Ajay (The Indian Journal of Agricultural Sciences, 2020)
A field experiment was conducted to study the influence of imidazolinones alone and in combination on pigeon pea [Cajanus cajan (L.) Millsp] at CCS Haryana Agricultural University, Hisar, India during 2017-18 and 2018-19. The experiment was laid out in randomized block design using 18 treatment combinations replicated thrice. During both the years, due to weed free condition, taller (272.3 cm) and heavier (200.1 g) plant at harvest, higher yield attributes (11.5 plants/m2 at harvest; 92.8 pods/plant; 3.30 seeds/pod and 7.22 g 100-seed weight) and productivity (1914, 6259 and 8172 kg/ha seed, stalk and biological yield, respectively and 23.4% harvest index) of pigeonpea was observed in weed free treatment which was closely followed by treatment where two hoeings at 40 and 70 DAS were employed. While comparing the different herbicides treatments, PRE application of pendimethalin + imazethapyr @ 1000 + 75 g/ha gave statistically at par productivity of pigeon peaas obtained in weed free condition. Therefore, PRE application of pendimethalin + imazethapyr @ 1000 + 75 g/ha proved to be an effective and a profitable alternative to the existing recommendation (two hoeings at 25 and 45 DAS) of weed control in pigeonpea in Haryana.